Pre-procedural CT angiography inferior vena cava measurements: a predictor of mortality in patients undergoing transcatheter aortic valve implantation - Eberhard, Matthias; Milanese, Gianluca; Ho, Michael; Zimmermann, Stefan; Frauenfelder, Thomas; Nietlispach, Fabian; Maisano, Francesco; Tanner, Felix C.; Nguyen-Kim, Thi Dan Linh (European radiology, 2019)
Objectives To assess the value of pre-procedural computed tomography angiography (CTA) measurements of the suprahepatic inferior vena cava (IVC) to detect elevated central venous pressure (CVP) assessed by right heart catheterisation (RHC), and to predict post-procedural 1-year mortality in a cohort of patients undergoing transcatheter aortic valve implantation (TAVI). Methods We retrospectively evaluated 408 consecutive patients undergoing CTA before TAVI between January 2011 and December 2014. Two hundred and five patients were included in the RHC cohort, who underwent RHC and CTA within ≤1 day prior to TAVI. Two hundred and three patients not fulfilling this requirement were included in the validation cohort. Measurements of the IVC were performed between diaphragm and right atrium on axial slices. Receiver operating characteristic (ROC) analyses, Kaplan-Meier analyses and Cox regression analyses were performed. Results In the RHC cohort, ROC curve analyses for IVC area measurements indicated an AUC of 0.77 ( p < 0.001) to detect CVP ≥10mmHg and an area under the ROC curve (AUC) of 0.72 ( p < 0.001) to predict 1-year mortality. An IVC area cut-off of ≥665 mm 2 predicted 1-year mortality with a specificity of 84% and a sensitivity of 63%. Kaplan-Meier analysis showed that patients with an IVC area ≥665 mm 2 had a significantly higher post-procedural 1-year mortality (38% versus 7%, log-rank p < 0.001) with a hazard ratio of 5.5 (95% CI, 2.2-13.6; p < 0.001). Applying this cut-off value to the validation cohort confirmed a significantly higher 1-year mortality after TAVI (34% versus 11%; log-rank p = 0.004) for patients with an IVC area ≥665 mm 2 . Conclusions Pre-procedural enlargement of the suprahepatic IVC is a predictor of post-procedural 1-year mortality in patients evaluated for TAVI. Key Points • IVC measurements are moderate predictors of an elevated CVP in TAVI patients. • Pre-procedural IVC enlargement is a predictor of 1-year mortality after TAVI. • IVC enlargement is associated with right heart dysfunction in TAVI patients.